The Relationship between Body Image Dissatisfaction and New Anthropometric Indices in Women Referred to the Nutrition Clinic in Northwest of Iran, Ardabil City, 2019 - Fatemeh Ghannadiasl; Neda Hoseini (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Introduction: Recent studies have shown a high prevalence of body image dissatisfaction in women. This study purposed to examine the relationship between body image dissatisfaction and new anthropometric indices in women. Methods: A cross-sectional study was done among 384 women referred to the nutrition clinic in Ardabil city in 2019, using convenience sampling method. Data were collected through multidimensional body self-relations questionnaires and anthropometric measurements. This questionnaire is an attitudinal assessment of body image, using a 5-point disagrees-agree Likert scale to collect responses. Data was analyzed using SPSS software (version 21). The Pearson correlation coefficient was used to investigate the relation between body image dissatisfaction and anthropometric indices. The significance level was less than 0.05. Results: The mean age and body mass index (BMI) of the women under study were 30.01±7.20 years and 30.21±5.17kg/m2, respectively. Correlation analysis presented that a significant positive relationship was between all anthropometric indices and the subjective weight and overweight preoccupation subscales. The highest relationship of subjective weight subscale was found with BMI, waist circumference, and waist-to-height ratio (WHtR) (r=0.85, p<0.001) followed by abdominal volume index (AVI) (r=0.82, p<0.001). The highest relationship of the overweight preoccupation subscale was obtained with waist circumference (r=0.44, p<0.001) followed by AVI and weight (r=0.42, p<0.001) and WHtR (r=0.41, p<0.001). Conclusion: Body image dissatisfaction was associated with anthropometric indices. The findings indicated the need for interventions designed to improve anthropometric indices and, consequently, body image dissatisfaction